Phylodynamics of sunflower chlorotic mottle virus, an emerging pathosystem - Cabrera Mederos, Dariel; Torres, Carolina; Bejerman, Nicolás; Trucco, Verónica; Lenardon, Sergio; Leiva Mora, Michel; Giolitti, Fabián (Virology (New York, N.Y.), 2020)
Distribution and epidemiological patterns of sunflower chlorotic mottle virus (SCMoV) in sunflower (Helianthus annuus L.) growing areas in Argentina were studied from 2006 to 2017. The virus was detected exclusively in the Pampas region (Entre Ríos, Santa Fe, Córdoba, La Pampa and Buenos Aires provinces). Phylodynamic analyses performed using the coat protein gene of SCMoV isolates from sunflower and weeds dated the most recent common ancestor (MRCA) back to 1887 (HPD95% = 1572–1971), which coincides with the dates of sunflower introduction in Argentina. The MRCA was located in the south of Buenos Aires province and was associated with sunflower host (posterior probability for the ancestral host, ppah = 0.98). The Bayesian phylodynamic analyses revealed the dispersal patterns of SCMoV, suggesting a link between natural host diversity, crop displacement by human activities and virus spread.